Disseminated intravascular coagulation and the Waterhouse-Friderichsen syndrome. Issue 249 (October 1971) - Fox, B.
Abstract : In a clinico-pathological study of 13 children who died with Waterhouse-Friderichsen syndrome, there were deposits of fibrin in many organs, especially the adrenal glands and the kidneys. This finding supports the hypothesis that disseminated intravascular coagulation (DIC) occurs in this syndrome. The exact role that DIC plays has not been defined; though it probably contributes to the severe shock and the widespread haemorrhages; the adrenal haemorrhages appear not to be due directly to DIC. The presence of DIC in the Waterhouse-Friderichsen syndrome suggests that heparin should be a logical form of treatment.